Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s00395-010-0085-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and ultrastructural studies in dilated cardiomyopathy patients: a large deletion in the lamin A/C gene is associated with cardiomyocyte nuclear envelope disruption

Abstract: Major nuclear envelope abnormalities, such as disruption and/or presence of intranuclear organelles, have rarely been described in cardiomyocytes from dilated cardiomyopathy (DCM) patients. In this study, we screened a series of 25 unrelated DCM patient samples for (a) cardiomyocyte nuclear abnormalities and (b) mutations in LMNA and TMPO as they are two DCM-causing genes that encode proteins involved in maintaining nuclear envelope architecture. Among the 25 heart samples investigated, we identified major car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 54 publications
5
76
0
Order By: Relevance
“…The structural hypothesis states that mutations within lamin A/C lead to disorganization of the proteinaceous meshwork, instability of the nuclear envelope and disorganization of chromatin, which in turn leads to the overall inability of the cell to properly function in contracting tissue environment such as striated muscles [46,47]. Building on this hypothesis, recent studies identified repetitive disruptions of the nuclear envelope in the presence of lamin A/C mutations [17,48]. These disruptions impaired protein distribution into cell compartments.…”
Section: Conclusion: the Mechanistic Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural hypothesis states that mutations within lamin A/C lead to disorganization of the proteinaceous meshwork, instability of the nuclear envelope and disorganization of chromatin, which in turn leads to the overall inability of the cell to properly function in contracting tissue environment such as striated muscles [46,47]. Building on this hypothesis, recent studies identified repetitive disruptions of the nuclear envelope in the presence of lamin A/C mutations [17,48]. These disruptions impaired protein distribution into cell compartments.…”
Section: Conclusion: the Mechanistic Hypothesesmentioning
confidence: 99%
“…These disruptions impaired protein distribution into cell compartments. Translocations of large amounts of protein into the cytoplasm could trigger aggresome formation or even induce cell apoptosis [48]. On the other hand, translocation of transcription factors into the cytoplasm might impair gene expression.…”
Section: Conclusion: the Mechanistic Hypothesesmentioning
confidence: 99%
“…The mutation that we describe is the first complex deletion in this gene reported. A large deletion encompassing exon 3 to 12 was described by Gupta et al 34 in a 39-year-old woman with ventricular arrhythmias and mild dilatation and normal function. PCR analysis for the 566-bp fragment specific for our deletion on genomic DNA from this woman did not result in an amplification product, suggesting that although the mutation encompassed the same region, a different mutational event could underlie the disorder (Fré-dérique Tesson, personal communication).…”
Section: Discussionmentioning
confidence: 94%
“…29 Laminopathies result primarily from missense mutations. 10,22 Nonsense 30 mutations, splice-site 31 mutations, small insertions 32 /deletions, 33 as well as large deletions 28,34 are less common. The mutation that we describe is the first complex deletion in this gene reported.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiomyocytes of these patients demonstrate nuclear envelope abnormalities, changes in lamins expression and mitochondria miss-localization. 28,29 C. elegans pharynx is often used as a model of the function and muscular composition of the human heart. 30 In our analysis, we detected down regulation of several genes involved in the proper function and structure of the pharyngeal muscle; abu-6, abu-7, abu-8 and abu-15 (homologs of Keratinassociated protein 10-4) have a role in protecting against miss-folded protein stress, as well as proper pharyngeal grinder function; act-1 is required for pharyngeal muscle structures and myo-2 (human myosin heavy chain ortholog) encodes a muscle pharynx specific myosin heavy chain isoform.…”
Section: Down Regulation Of Pharyngeal Muscle Genes Correlates With Amentioning
confidence: 99%